PROTECTION OF CHILDREN AS A PHILOSOPHICAL AND SOCIOLOGICAL BASE FOR THE AGE LIMIT: MAQĀṢID SHARĪʻA VERSION OF JASSER AUDA - Ayu, Rizqa Febry; Kamsi (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2022)
This study examines how Jasser Auda’s maqāṣid sharia view son child protection as the basis for determining the age limit for marriage and how Jasser Auda’s maqāṣid sharia view son the philosophical and sociological foundations contained in the marriage age limit. This study uses a qualitative study with a descriptive analytical method with a philosophical and sociological approach. The results of this study indicate that, First, Jasser Auda’s maqāṣid sharia view on child protection as the basis for determining the age limit for marriage, namely that Jasser Auda’s maqāṣid asy-syarīʻah theory shows that the goal of equalizing the marriage age limit contained in Law Number 16 The year 2019 refers to the concept of child protection as regulated in concerning Child Protection which includes the basic rights of children, the right to protection from violence and discrimination and full justice for children. Second, Jasser Auda’s maqāṣid sharia view of the philosophical and sociological foundations contained in the marriage age limit in using six features of the system theory that Jasser Auda optimized the results according to Cognitive, Openness, Wholeness, Interrelated Hierarchy, Multi Dimensionality and Purposefulness is accordance with maqāṣid sharia, realizing the goal of eliminating discrimination against women accordance with the global era by reforming maqāṣid to words Human Rights, creating equality between men and women, refers to the environment of society, nation and state, such as upholding justice and tolerance, achieving a harmonious family.